Genocide, collective violence, and popular memory : the politics of remembrance in the twentieth century - Lorey, David E.; Beezley, William H. (Wilmington, Del. : SR Books, 2002)
In Genocide, Collective Violence, and Popular Memory: The Politics of Remembrance in the Twentieth Century, the editors present and discuss the many different social responses to the challenge of coming to terms with past reigns of terror and collective violence. Designed for undergraduate courses in political violence and revolution, this volume treats a wide variety of incidents of collective violence-from decades-long genocide to short-lived massacres. The selection of essays provides a broad range of thought-provoking case studies from Latin America, Africa, Europe, and Asia. This provocat.
Germany and Japan: Legacies of World War10 -- War Stories; Notes; 11 -- Photography, National Identity, and the "Cataract of Times"; Notes; Suggested Reading.
Print version record.
Includes bibliographical references.
English.
eBooks on EBSCOhost
Keywords: Genocide -- Psychological aspects; Genocide -- History -- 20th century; Memory -- Social aspects; World politics -- 20th century; Politique mondiale -- 20e siècle.; SOCIAL SCIENCE -- Demography; Genocide; Genocide -- Psychological aspects; Memory -- Social aspects; World politics; Völkermord; Kollektives Gedächtnis; Aufsatzsammlung; Kollektive Gewalt; Kulturvergleich; Genocide; Herdenkingen; Génocide -- 20e siècle.; Mémoire collective -- 20e siècle.; 1900-1999; History